Exploring horizontal and vertical genetic structuring in Pocillopora populations in Reunion Island (southwestern Indian Ocean): insight for the ‘Deep Reef Refuge’ hypothesis? - Jeanne Guibert; Aurélien Fajeau; Ludovic Hoarau; Mehdi Adjeroud; Lucie Penin; Nicolas Oury; Hélène Magalon (Coral Reefs, 2026)

Operationalizing enabling conditions: a social-ecological perspective on marine conservation success - Jessica Salaün; Mohsen Kayal; Jean Wencélius; Pauline Fabre; Lauric Thiault; Mehdi Adjeroud; Tamatoa Bambridge; Sébastien Galliot; Malika René-Trouillefou; Joachim Claudet (Sustainability Science, 2026)

Coral recruitment in mesophotic coral ecosystems is lower and taxonomically distinct from shallow environments at Reunion Island, southwestern Indian Ocean - Ludovic Hoarau; François Guilhaumon; Sophie Bureau; Priscille Labarrère; Lionel Bigot; Mehdi Adjeroud; Lucie Penin (Coral Reefs, 2025)

Assessing recovery potential of coral reefs in Madagascar and the effects of marine protected areas - Mahery Randrianarivo; Lahitsiresy Max Gasimandova; Johanès Tsilavonarivo; Andriamanjato Razakandrainy; Jacques Philippe; François Guilhaumon; Radonirina Lebely Botosoamananto; Lucie Penin; Gildas Todinanahary; Mehdi Adjeroud (Regional Studies in Marine Science, 2024)

Changes of Tiahura (Moorea Island) reef flat habitats using 67 years of remote sensing observations - Clémentine Violette; Mehdi Adjeroud; Claude Payri; Sam J. Purkis; Serge Andréfouët (Coral Reefs, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Coral recruitment in the Toliara region of southwest Madagascar: Spatio‐temporal variability and implications for reef conservation - Radonirina Lebely Botosoamananto; Gildas Todinanahary; Lahitsiresy Max Gasimandova; Mahery Randrianarivo; François Guilhaumon; Lucie Penin; Mehdi Adjeroud (Marine Ecology, 2024)
Investigating coral recruitment is critical to better understand replenishment and resilience capacities of coral reef ecosystems and to improve their conservation. Here, we examined the spatio‐temporal patterns of coral recruitment and the influence of confamilial adult coral cover in the region of Toliara, southwest Madagascar. Terracotta tiles were immersed from October to late January over a 3‐year period (2018–2021) at 10 stations located on major reef habitats. Overall recruitment rates were relatively high compared to those of other reefs in the Southwestern Indian Ocean, ranging from 219.20 recruits.m −2 in 2018–2019 to 156.30 recruits.m −2 in 2020–2021. Recruit assemblages were dominated by Acroporidae (45.5%) and Pocilloporidae (45.0%), whereas Poritidae (1.9%) and “other” recruits (3.6%) were rarely recorded. Recruitment patterns varied among stations and habitats, with higher rates in patch reef (187.06 recruits.m −2 ) and outer slope stations (156.99 recruits.m −2 ) compared to inner slope stations (108.04 recruits.m −2 ). With the exception of “other” recruits, recruitment rates decreased between 2018 and 2019 and 2019 and 2020, followed by an increase in 2020–2021 that reached or even exceeded initial values at some stations. The abundance of Pocilloporidae recruits was positively correlated with the cover of confamilial adult corals, highlighting potential stock–recruitment or recruitment–limitation relationships, or an aggregative settlement of young stages near the established adult colonies, whereas no such relationships were recorded for other coral family categories. This study identified sites on the outer slope and patch reefs to consider prioritizing for protection as recruitment hotspots, as well as degraded inner slope sites that could benefit from restoration, with the important caveat that any measures should be accompanied by alternative income‐generating activities through local involvement that suits the Malagasy context, such as locally marine managed areas.

Effects of Madagascar marine reserves on juvenile and adult coral abundance, and the implication for population regulation - Mahery Randrianarivo; Radonirina Lebely Botosoamananto; François Guilhaumon; Lucie Penin; Gildas Todinanahary; Mehdi Adjeroud (Marine Environmental Research, 2023)

Species and population genomic differentiation in Pocillopora corals (Cnidaria, Hexacorallia) - Didier Aurelle; Marine Pratlong; Nicolas Oury; Anne Haguenauer; Pauline Gélin; Hélène Magalon; Mehdi Adjeroud; Pascal Romans; Jeremie Vidal-Dupiol; Michel Claereboudt; Camille Noûs; Lauric Reynes; et al. (Genetica, 2022)

Spatial and temporal patterns in the coral assemblage at Clipperton Atoll: a sentinel reef in the Eastern Tropical Pacific - J. J. Adolfo Tortolero-Langarica; Eric Clua; Fabián A. Rodríguez-Zaragoza; Jennifer E. Caselle; Alma P. Rodríguez-Troncoso; Mehdi Adjeroud; Alan M. Friedlander; Amílcar L. Cupul-Magaña; Enric Ballesteros; Juan P. Carricart-Ganivet; Eric K. Brown (Coral Reefs, 2022)

Diving into the lower mesophotic coral ecosystems (65–93 m depth) of Reunion Island (Southwestern Indian Ocean) sheds light on the hidden diversity of hydroids (Cnidaria, Hydrozoa) - Nicole Gravier-Bonnet; Émilie Boissin; Ludovic Hoarau; Patrick Plantard; Camille Loisil; David Ory; Thierry Mulochau; Pascale Chabanet; Mehdi Adjeroud; Chloé Bourmaud; Héloïse Rouzé (Marine Biodiversity, 2022)

Two Hidden mtDNA-Clades of Crown-of-Thorns Starfish in the Pacific Ocean - Nina Yasuda; Jun Inoue; Michael R. Hall; Manoj R. Nair; Mehdi Adjeroud; Miguel D. Fortes; Mutsumi Nishida; Nat Tuivavalagi; Rachel Ravago-Gotanco; Zac H. Forsman; Taha Soliman; Ryo Koyanagi; et al. (Frontiers in Marine Science, 2022)
Recurring outbreaks of crown-of-thorns starfish (COTS) severely damage healthy corals, especially in the Western Pacific Ocean. To obtain a better understanding of population genetics of COTS and historical colonization across the Pacific Ocean, complete mitochondrial genomes were sequenced from 243 individuals collected in 11 reef regions. Our results indicate that Pacific COTS ( Acanthaster cf. solaris ) comprise two major clades, an East-Central Pacific (ECP) clade and a Pan-Pacific (PP) clade, separation of which was supported by high bootstrap value. The ECP clade consists of COTS from French Polynesia, Fiji, Vanuatu and the Great Barrier Reef (GBR). The Hawaii population is unique within this clade, while California COTS are included in EPC clade. On the other hand, the PP clade comprises multiple lineages that contain COTS from Vietnam, the Philippines, Japan, Papua New Guinea, Micronesia, the Marshall Islands, GBR, Vanuatu, Fiji and French Polynesia. For example, a lineage of the PP clade, which has the largest geographic distribution, includes COTS from all of these locations. These results suggest two alternative histories of current geographic distributions of COTS in the Pacific Ocean, an ECP clade ancestry or Western Pacific clade ancestry. Although further questions remain to be explored, this discovery provides an evolutionary context for the interpretation of COTS population structure which will aid future coral reef research in the Pacific Ocean, and ultimately improve reef management of COTS.

Juvenile corals underpin coral reef carbonate production after disturbance - Jérémy Carlot; Mohsen Kayal; Hunter S. Lenihan; Simon J. Brandl; Jordan M. Casey; Mehdi Adjeroud; Ulisse Cardini; Alexandre Merciere; Benoit Espiau; Diego R. Barneche; Alessio Rovere; Laetitia Hédouin; et al. (Global Change Biology, 2021)
Sea‐level rise is predicted to cause major damage to tropical coastlines. While coral reefs can act as natural barriers for ocean waves, their protection hinges on the ability of scleractinian corals to produce enough calcium carbonate (CaCO 3 ) to keep up with rising sea levels. As a consequence of intensifying disturbances, coral communities are changing rapidly, potentially reducing community‐level CaCO 3 production. By combining colony‐level physiology and long‐term monitoring data, we show that reefs recovering from major disturbances can produce 40% more CaCO 3 than currently estimated due to the disproportionate contribution of juvenile corals. However, the buffering effect of highly productive juvenile corals is compromised by recruitment failures, which have been more frequently observed after large‐scale, repeated bleaching events. While the size structure of corals can bolster a critical ecological function on reefs, climate change impacts on recruitment may undermine this buffering effect, thus further compromising the persistence of reefs and their provision of important ecosystem services.

Which Method for Which Purpose? A Comparison of Line Intercept Transect and Underwater Photogrammetry Methods for Coral Reef Surveys - Isabel Urbina-Barreto; Rémi Garnier; Simon Elise; Romain Pinel; Pascal Dumas; Vincent Mahamadaly; Mathilde Facon; Sophie Bureau; Christophe Peignon; Jean-Pascal Quod; Eric Dutrieux; Lucie Penin; et al. (Frontiers in Marine Science, 2021)
The choice of ecological monitoring methods and descriptors determines the effectiveness of a program designed to assess the state of coral reef ecosystems. Here, we comparer the relative performance of the traditional Line Intercept Transect (LIT) method with three methods derived from underwater photogrammetry: LIT on orthomosaics, photoquadrats from orthomosaics, and surface analyses on orthomosaics. The data were acquired at Reunion Island on five outer reef slopes and two coral communities on underwater lava-flows. Coral cover was estimated in situ using the LIT method and with LITs and photoquadrats digitized on orthomosaic. Surface analyses were done on the same orthomosaics. Structural complexity of the surveyed sites was calculated from digital elevation models using three physical descriptors (fractal dimension, slope, surface complexity), and used to explore their possible influence in coral cover estimates. We also compared the methods in terms of scientific outputs, the human expertise and time required. Coral cover estimates obtained with in situ LITs were higher than those obtained with digitized LITs and photoquadrats. Surfaces analyses on orthomosaics yielded the lowest but most the precise cover estimates (i.e., lowest sample dispersion). Sites with the highest coral cover also had the highest structural complexity. Finally, when we added scientific outputs, and requirements for human expertise and time to our comparisons between methods, we found that surface analysis on the orthomosaics was the most efficient method. Photoquadrats were more time-consuming than both in situ and digitized LITs, even though they provided coral cover estimates similar to those of digitized LITs and yielded more than one descriptor. The LIT in situ method remains the least time-consuming and most effective for species-level taxonomic identifications but is the most limited method in terms of data outputs and representativeness of the ecosystem.

Recent and old duplications in crustaceans “Internal Transcribed Spacer 1″: structural and phylogenetic implications - Alain Van Wormhoudt; Mehdi Adjeroud; Heloise Rouzé; Matthieu Leray (Molecular Biology Reports, 2019)

Critical Information Gaps Impeding Understanding of the Role of Larval Connectivity Among Coral Reef Islands in an Era of Global Change - Peter J. Edmunds; Shelby E. McIlroy; Mehdi Adjeroud; Put Ang; Jessica L. Bergman; Robert C. Carpenter; Mary A. Coffroth; Atsushi G. Fujimura; James L. Hench; Sally J. Holbrook; James J. Leichter; Soyoka Muko; et al. (Frontiers in Marine Science, 2018)

Reefs at the edge: coral community structure around Rapa, southernmost French Polynesia - Mehdi Adjeroud; Carden C. Wallace; Pauline Bosserelle; Claude Payri; Jean‐Louis Menou; Michel Pichon (Marine Ecology, 2016)
Rapa (27°36′ S, 144°20′ W) is a small (~40 km 2 ) volcanic island isolated in the Southern Austral Archipelago, where direct anthropogenic stressors are extremely limited. Here, we present the results of the first quantitative survey of coral community structure across habitats and depths around the island. Despite its geographical isolation in the depauperate South Central Pacific, its small size and unfavourable environmental conditions (competition with macroalgae, low sea surface temperatures, reduced reef accretion), the diversity of scleractinian corals at Rapa is particularly high (112 species from 32 genera, including 37 species of Acropora ) in comparison to other French Polynesian islands and subtropical Pacific locations. Our results indicate that the abundance (>100 colonies per 10 m 2 recorded at nine of the 17 sampling stations) and cover (>40% at four stations) of corals are relatively high for a marginal reef location. Strong spatial heterogeneity was found, with high variation in diversity, abundance, cover and community composition among stations. Variation in community composition was related to habitat types, with distinct assemblages among fringing reefs within bays, reef formations at bay entrances, and those on the submerged platform surrounding the island. On the platform, a depth gradient was detected, with generic richness, abundance and cover generally greater at deeper stations (18–20 m depth) compared with medium‐depth (10–12 m) and shallow (1–3 m) stations. A gradient was also recorded along bays, with increasing coral diversity and abundance from the bay heads to the bay entrances. The coral community at Rapa was characterized by the presence of several taxa not found in other French Polynesian archipelagos and the rarity of others that are common and abundant in the Society and the Tuamotu islands. Another distinctive feature of reef communities at Rapa is the high cover and dominance of macroalgae, particularly in the shallower parts of the surrounding platform, which probably explains the lower densities of coral colonies recorded there. These characteristics of the diversity and biogeographical composition of coral assemblages at Rapa provide considerable ecological grounds for its conservation.

Genetic connectivity of the coral‐eating sea star A canthaster planci during the severe outbreak of 2006–2009 in the S ociety I slands, F rench P olynesia - Nina Yasuda; Coralie Taquet; Satoshi Nagai; Terutoyo Yoshida; Mehdi Adjeroud (Marine Ecology, 2015)
Occasional population outbreaks of the crown‐of‐thorns sea star, A canthaster planci , are a major threat to coral reefs across the Indo‐Pacific. The presumed association between the serial nature of these outbreaks and the long larval dispersal phase makes it important to estimate larval dispersal; many studies have examined the population genetic structure of A . planci for this purpose using different genetic markers. However, only a few have focused on reef‐scale as well as archipelago‐scale genetic structure and none has used a combination of different genetic markers with different effective population sizes. In our study, we used both mt DNA and microsatellite loci to examine A . planci population genetic structure at multiple spatial scales (from DNA (global F ST = −0.007, P = 0.997) and low levels of genetic structure using microsatellite loci (global F ST = 0.006, P = 0.005). We found no significant isolation by distance patterns within the study area for either genetic marker. The overall genetically homogenized pattern found in both the mitochondrial and nuclear loci of A . planci in the Society Archipelago underscores the significant role of larval dispersal that may cause secondary outbreaks, as well as possible recent colonization in this area.

Genetic diversity, clonality and connectivity in the scleractinian coral Pocillopora damicornis: a multi-scale analysis in an insular, fragmented reef system - Mehdi Adjeroud; Aurélie Guérécheau; Jeremie Vidal-Dupiol; Jean-François Flot; Sophie Arnaud-Haond; François Bonhomme (Marine Biology, 2014)

Coral assemblages in Tonga: spatial patterns, replenishment capacities, and implications for conservation strategies - Mehdi Adjeroud; Marine J. Briand; Mohsen Kayal; Pascal Dumas (Environmental Monitoring and Assessment, 2013)

Response of coral assemblages to thermal stress: are bleaching intensity and spatial patterns consistent between events? - Lucie Penin; Jeremie Vidal-Dupiol; Mehdi Adjeroud (Environmental Monitoring and Assessment, 2013)

Associational refuges among corals mediate impacts of a crown-of-thorns starfish Acanthaster planci outbreak - Mohsen Kayal; Hunter S. Lenihan; Cédric Pau; Lucie Penin; Mehdi Adjeroud (Coral Reefs, 2011)

Effects of predators and grazers exclusion on early post-settlement coral mortality - Lucie Penin; François Michonneau; Andrew Carroll; Mehdi Adjeroud (Hydrobiologia, 2011)

Small-scale variability in the size structure of scleractinian corals around Moorea, French Polynesia: patterns across depths and locations - Mehdi Adjeroud; Morgan S. Pratchett; Marie C. Kospartov; Christophe Lejeusne; Lucie Penin (Hydrobiologia, 2007)

Factors influencing spatial distribution of fish communities on a fringing reef at Mauritius, S.W. Indian Ocean - Mehdi Adjeroud; Yves Letourneur; Michel Porcher; Bernard Salvat (Environmental Biology of Fishes, 1998)

Long-term changes of epibenthic macrofauna communities in a closed lagoon (Taiaro Atoll, French Polynesia): 1972–1994 - Mehdi Adjeroud (Hydrobiologia, 1997)